Multilateral development aid: Assessing the major replenishments of 2016 - Richard Manning (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This survey of the 2016 replenishments of three multilateral development bank soft funds and of the Global Fund for AIDS, TB and Malaria shows that a significant re-set of the multilateral development finance system is taking place, with grant funding from traditional donors generally in decline (the Global Fund is an exception), but with the accessing of the 'hidden equity' in soft loan-based funds offering a large increase in such funding (most notably in the World Bank's soft fund, the International Development Association). 'Graduation' of countries away from eligibility for highly concessional multilateral finance is also changing the context. This paper underlines the need for more consideration of these wider structural issues.
Keywords: F35; F53; F63; O19; P45; 330; aid; multilateral finance; traditional and emerging donors; development; replenishments